Proteomics as a tool for live attenuated influenza vaccine characterisation. Issue 4 (22nd January 2020) - Hawksworth, Amy; Jayachander, Mahesh; Hester, Svenja; Mohammed, Shabaz; Hutchinson, Edward
Abstract: Many viral vaccines, including the majority of influenza vaccines, are grown in embryonated chicken eggs and purified by sucrose gradient ultracentrifugation. For influenza vaccines this process is well established, but the viral strains recommended for use in vaccines are updated frequently. As viral strains can have different growth properties and responses to purification, these updates risk changes in the composition of the vaccine product. Changes of this sort are hard to assess, as influenza virions are complex structures containing variable ratios of both viral and host proteins. To address this, we used liquid chromatography and tandem mass spectrometry (LC-MS/MS), a flexible and sensitive method ideally suited to identifying and quantifying the proteins present in complex mixtures. By applying LC-MS/MS to the pilot scale manufacturing process of the live attenuated influenza vaccine (LAIV) FluMist® Quadrivalent vaccine (AstraZeneca), we were able to obtain a detailed description of how viral and host proteins are removed or retained at each stage of LAIV purification. LC-MS/MS allowed us to quantify the removal of individual host proteins at each stage of the purification process, confirming that LAIV purification efficiently depletes the majority of host proteins and identifying the small subset of host proteins which are associated with intact virions. LC-MS/MS also identified substantial differences in the retention of the immunosuppressive viral protein NS1 in purified virions. Finally, LC-MS/MS allowed us to detect subtle variations in the LAIV production process, both upstream of purification and during downstream purification stages. This demonstrates the potential utility of LC-MS/MS for optimising the purification of complex biological mixtures and shows that it is a promising approach for process optimisation in a wide variety of vaccine manufacturing platforms.